PELATIHAN PENINGKATAN KUALITAS SOHUN SEBAGAI PRODUK UNGGULAN DESA PUCANG MILIRAN, KECAMATAN TULUNG KABUPATEN KLATEN - Eskasari Putri; Christiana Shinta Indhiarti; Wayan Novitasari (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2020)
Society dedication of UMS aims to upgarade the prosperty society through increasing of comprehension society about how to make Sohun that are hygienic, clean, and healty to be more competitive.The Benefits of this society dedication are quality upgrading of Sohun for the best product of Pucangmiliran Village, Tulung District, Klaten Regency. The benefits of this society dedication are directed to business continuity in a sustainable business world so that the standard of living society and the prosperity society are resolved. Collaboration society methods with lecture, training, and discussions. The training will be do for six month.